2002
DOI: 10.1007/bf02987317
|View full text |Cite
|
Sign up to set email alerts
|

Sulphonated aromatic pollutants

Abstract: Many synthetic sulphonated aromatic compounds are used as starting material to produce dyes and pigments, or are released as by-products in the effluents of the textile and dye industry. A large number of these chemicals are poorly biodegradable and cannot be eliminated by classical wastewater treatment plants. To limit the impact of these pollutants on the environment, new processes, based on the use of higher plants (constructed wetlands or hydroponic systems), are under development. Detergents and surfactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Many studies have shown that the different species of Pseudomonas are able to degrade the synthetic dyes mainly azo dye in the liquid medium and have been used for the treatment of textile e uent [23]. Moreover, many sulphonated aromatic compounds are utilized by dye manufacturing industries as primary materials to produce dyes and many of them are released as byproducts in the e uents coming from textile industries [10]. Besides, the textile industry is widely using Na 2 SO 4 in dying process and sulphuric acid for maintaining the pH within the wastewater treatment plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the different species of Pseudomonas are able to degrade the synthetic dyes mainly azo dye in the liquid medium and have been used for the treatment of textile e uent [23]. Moreover, many sulphonated aromatic compounds are utilized by dye manufacturing industries as primary materials to produce dyes and many of them are released as byproducts in the e uents coming from textile industries [10]. Besides, the textile industry is widely using Na 2 SO 4 in dying process and sulphuric acid for maintaining the pH within the wastewater treatment plants.…”
Section: Discussionmentioning
confidence: 99%
“…The wastewater generated from the small scale industries contains the complex mixture of the manufacturing of textile dyes, paints, chemicals, solvents, and textile released wastewater [10]. Hence, the microbial community present in such ecosystem are exposed to diverse array of substrates and are responsible for the degradation capacity of these molecules in the target niche.…”
Section: Introductionmentioning
confidence: 99%
“…elimination of these pollutants from industrial effluents would be welcome and useful [13]. Plant metabolism is extremely diverse and could be very useful for treatment of recalcitrant compounds at low cost and with low maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic surfactants have many applications and high consumption rates in different fields including household cleaning detergents, personal care products, textiles and pesticide formulations, etc. [3,[9][10][11]. Previous researches documented that the engineered surfactants were toxic to microorganisms, plants (e.g., Sorghm bicolour, Helianthuus annuus, Phaseolus aureus, etc.…”
Section: Introductionmentioning
confidence: 99%